CAT Swarm Optimization Algorithm for Data Aggregation in UAV Assisted in UWSN - V. , Nagaraju; G. , Komala Valli; A. , Krishna Prabha; T. , Raghavi (International Journal of Psychosocial Rehabilitation, 2020)
Underwater communication is a challenging technology in wireless communication, and the cost of underwater sensor network deployment is still very high. Most applications of underwater cyber-physical systems (UCPS) have a demand for reliable data collection in an efficient and timely manner. The challenging task to aggregate data is the energy-constrained characteristic of acoustic communication. In this, the energy optimization for efficient data collection in UCPS over autonomous underwater vehicle (AUV)-assisted underwater acoustic sensor networks. To promote better data transferring in underwater environments, we consider the energy and lifetime of the network. To decrease energy utilization and promote the underwater lifetime, the Cat Swarm Optimization Algorithm is used for sensor deployment to efficiently aggregate data from the underwater acoustic sensor nodes.